Kondisi Sosial Ekonomi Petani Gambir Di Kenagarian Ganting Mudiak Selatan Surantih Kecamatan Sutera Kabupaten Pesisir Selatan - Rinaldo, Depi; Juita, Erna; Keslan, Widya Prari (STKIP PGRI Sumbar, 2013)
The agricultural sector still plays a leading role in Indonesia, because the majority of Indonesias population still lives and works as a farmer so that it can be said that agriculture is the backbone of life. Agricultural development in Indonesia aimed at increasing revenue, welfare, and public access through the development of agriculture in the process of improving the quality and quantity of production and distribution as well as the diversity of agricultural products, one of which can be enhanced through the development of business gambier agriculture. Associated with this study aimed to obtain data or information about the socio-economic conditions of farmers gambier In Kenagarian Ganting Mudiak Selatan Surantih Kacamatan Sutera Kabupaten Pesisir Selatan.Type of research is classified in descriptive research. The study population was farmers gambier In Kenagarian Ganting South Mudiak Selatan Surantih Kacamatan Sutera Kabupaten Pesisir Selatan. Samples were taken with a proportional random sampling technique with the proportion of 30%, the sample totaled 111 households. Guided data collection questionnaire, the analysis used was descriptive statistics using the percentage formula and TCR.The results showed that: 1) The condition gambier farmers income: source of income of the husband, availability of sufficient food,Â expenditure average in 1 month for food> Rp 750.000-1000.000 and expenditures for food in one month than an average <Rp 500,000, 2) the health condition of gambier farmers generally good, but in meeting the needs of health is still lacking, 3) housing conditions gambier farmers: the status of ones own home is a home, building condition wood / board, 2 pieces of rooms, house building area is less than 7 , 2 m ^ 2 and a source of home lighting on average of PLN, 4) socio-cultural relations are generally good gambier farmers (87.5%). The prevailing culture of life amid gambier farmers generally current mediocrity.